Intervenções curriculares estruturadas a partir da abordagem temática: desafios e potencialidades - Ferreira, Marinês Verônica (2016)
With this research, it was sought to signal referrals to form structured curriculum by thematic approach, with the research problem: what have been the data referrals, challenges and potential found in structured curricular interventions according to the thematic approach in Science Nature, in public high schools in Santa Maria / RS? As a general objective: to identify, analyze and socialize curricular settings, in the area of Natural Sciences, structured by thematic approach. With specific objectives, it was sought to: identify schools and/or pedagogical practices that work curricular interventions as the thematic approach; analyze assumptions and forwards data to the identified practices; identify challenges and potentials found in working with the thematic approach; signal referrals curriculum guided by the thematic approach. The theoretical framework underpinning this work were based on the assumptions of Freirean Thematic Approach. In order to achieve these objectives outlined, a qualitative research, which was attended by thirteen (13) teachers in the field of Natural Sciences, who worked in high school in four (4) state network schools in Santa Maria/RS, constituting a sample six (6) curriculum interventions. The instrument used to construct the material analyzed was the semi-structured interview with teachers and analysis followed the assumptions of Textual Analysis Discourse (ATD). Analysis process emerged two broad categories: one that relates to the challenges and the other to labor potential in view of the thematic approach. In the first category are listed the challenges, called subcategories, which emerged from the curricular interventions: Initial teacher education: difficulties in the development of curricular interventions in the context of themes; Thematic Research: limits indicated in the theme definition in the curriculum interventions; curricular interventions: difficulties regarding the organization of time for planning at school and interdisciplinarity: challenges to be faced. In a second step, the potential is identified, also constituting subcategories, which originated from the curricular interventions: Collective work: potential from curricular interventions; teaching collective work: Potential from curricular interventions; Motivation: outstanding potential in the development of work and curriculum interventions from thematic approach: learning as highlighted potential. It is understood that this work will contribute to give visibility to the curriculum reorientation of practices that are being developed in school environments, favoring the teaching reflection about both the potential and the minimization of the difficulties experienced by alternative curriculum interventions.